Synthesis of NiMnSn single crystals - Dunn, Adam James. (2011)
A class of magnetocaloric materials of current interest is that of the Ni-Mn-Sn Heusler alloys. This material exhibits an inverse magnetocaloric effect (IMCE), which occurs at a first-order phase transformation temperature under the application of adiabatic magnetisation. The system then transits from a high temperature austenite phase to a low temperature martensite phase, creating a cooling effect. This magnetocaloric effect (MCE) is three times larger than traditionally studied inverse IMCE materials. A composition of Ni50Mn37Sn13, exhibits an IMCE at room temperature, which is promising for future magnetic refrigeration purposes that are an environmentally friendly alternative to vapour-compression refrigeration technology. Current studies have reported the IMCE of polycrystalline samples. Single crystals of the composition Ni50Mn37Sn13 are believed to exhibit larger and enhanced IMCE properties. In this report, two crystal growth methods were used to grow high quality Ni50Mn37Sn13 single crystals. A single crystal of atomic composition Ni49.13Mn35.33Sn15.53 was produced by the optical floating zone technique, while the attempt to grow Ni-Mn-Sn from the high-temperature solution (Sn Flux) resulted in a single crystal of stiochiometric composition MnSn2, Structures of the crystals were characterised by powder X-ray diffraction and single crystal X-ray diffraction. The composition was determined by energy dispersive spectroscopy. The quality of crystals was studied on etched and polished cross-sections cut perpendicular and horizontal to the sample growth directions. Differential scanning calorimetry technique, determined the first-order phase transformation was below 100K. Vibrating sample magnetometery, with temperature range 90K - 440K verified the presence of an austenite Curie temperature at 375K.